2008
DOI: 10.1016/j.laa.2007.07.026
|View full text |Cite
|
Sign up to set email alerts
|

IMRT treatment planning for prostate cancer using prioritized prescription optimization and mean-tail-dose functions

Abstract: Treatment planning for intensity modulated radiation therapy (IMRT) is challenging due to both the size of the computational problems (thousands of variables and constraints) and the multi-objective, imprecise nature of the goals. We apply hierarchical programming to IMRT treatment planning. In this formulation, treatment planning goals/objectives are ordered in an absolute hierarchy, and the problem is solved from the top-down such that more important goals are optimized in turn. After each objective is optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 14 publications
0
30
0
4
Order By: Relevance
“…As previous studies have shown, a small relaxation of a higher-priority objective can result in a large improvement of a lower-priority goal [12], [13]. The studies indicated that, in the reduced-order space, the slip factor could significantly improve the average dose at the OARs, without significantly compromising the dose homogeneity at the PTV.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As previous studies have shown, a small relaxation of a higher-priority objective can result in a large improvement of a lower-priority goal [12], [13]. The studies indicated that, in the reduced-order space, the slip factor could significantly improve the average dose at the OARs, without significantly compromising the dose homogeneity at the PTV.…”
Section: Discussionmentioning
confidence: 91%
“…have previously suggested using ‘mean tail dose’ rather than conventional dose-volume constraints [30], which are linear functions and hence, computationally attractive. ‘Mean tail dose’ refers to the mean dose of either the hottest or coldest specified fractional volume and has been successfully used in PO studies in the past [13]. However, one disadvantage of the ‘mean tail dose’ approach is the increase in problem size, which would result in extensive execution times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Güray and Güler (2013) proposed a hierarchical goal-programming (HGP) model to address scheduling problem of residents and the senior academic staff to outpatient clinics (OCs) in a physical medicine and rehabilitation (PMR) department. In the past significant amount of research have been conducted using MODM approaches to deal with optimizations regarding cancer treatment planning (Pugachev and Xing 2002;Clark et al 2008;Craft et al 2012;Bertsimas et al 2013;Chan et al 2014). Most of the articles related to optimization for cancer treatment focus on beam angles and IMRT features, while there is lack of enough articles on dose planning optimization and for prostate cancer specifically.…”
Section: Introductionmentioning
confidence: 99%
“…CHO is an automated planning process developed at Memorial Sloan Kettering Cancer Center. It is based on the optimization technique named hierarchical constrained optimization . CHO respects clinical priorities and produces Pareto optimal plans.…”
Section: Introductionmentioning
confidence: 99%